A comparative analysis of two writing styles: Latin American magical realism represented by García Márquez's One Hundred Years of Solitude and Chinese hallucinatory realism represented by Mo Yan's Life and Death Are Wearing Me Out - Yuan, Yuan (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2022)
In 2012, Chinese writer Mo Yan was awarded the Nobel Prize for Literature. His work differs from traditional socialist realism but draws on the writing techniques of many world literature, including Latin American magical realism. Therefore, his professions are considered to blossom Latin American magical realism in China. However, this article argues that he studied not only Latin American literature but also the writing styles of many other foreign literary works and formed his unique style based on the inheritance of his native culture. It would be inaccurate to describe Mo Yan's work style solely in Latin American magical realism. This article argues that Mo Yan's hallucinatory realism is strongly characterized by indigenous Chinese literature and its characteristics and that his Life and Death Are Wearing Me Out is a beautiful flower in the garden of world literature, along with García Márquez's One Hundred Years of Solitude. This dissertation uses comparative research to study the differences between Latin American magical realism and Mo Yan’s hallucinatory realism. Through the comparative research method between One Hundred Years of Solitude and Life and Death Are Wearing Me Out, we understand the differences between Latin American magical realism and Mo Yan’s hallucinatory realism between the two places. At the same time, this study uses a comparative approach to understand that Mo Yan and García Márquez, despite being in two different places, both use many of the same writing techniques, and of course, both present different literary landscapes in their respective continents. This is rich in significance for future literary comparisons between China and the rest of the world.
Keywords: Comparative Literature